The dsRNA Delivery, Targeting and Application in Pest Control - Yuzhen Lu; Xinyue Deng; Qijun Zhu; Denghui Wu; Jielai Zhong; Liang Wen; Xiaoqiang Yu (Agronomy, 2023)
RNA interference (RNAi) is a simple and rapid method for silencing genes in various organisms, and it is widely used in gene function and genetics research. RNAi has been developed as a novel pest management strategy. Double-stranded RNAs (dsRNAs) delivered via microinjection, ingestion, or soaking are effective for silencing genes in insect pests, whereas oral and topical delivery methods are feasible for field applications. Here, we summarize oral and topical delivery, in pests, of dsRNA target genes, including those involved in energy metabolism, synthesis of essential cellular components, hormone homeostasis, chitin metabolism, the digestive system, immunity, detoxification, insecticide resistance, and other processes. RNAi pesticides have been developed in the form of genetically modified (GM) crops expressing dsRNAs as well as applied as foliar sprays. In this review, RNAi-based products are also summarized.